Contribution of Organizational Learning and Market Orientation on Business Unit Performance Mediated by Job Satisfaction at Dairy Cattle Milk Cooperatives in East Java, Indonesia - Idrus, Salim Al; Ahmar, Ansari Saleh; Abdussakir, Abdussakir (Journal of Reviews on Global Economics, 2018)
Dairy cattle milk cooperatives in East Java has been threatened to be failure in achieving the target of Milk Self-Capacity By 2020. The reason of this failure threat is low productivity among dairy cattle milk entrepreneurs. Productivity is closely related with performance of dairy cattle milk business units, but this performance is affected by factors such as organizational learning, market orientation and job satisfaction. The objective of this research is to understand the contribution of organizational learning and market orientation on business unit performance through mediation of job satisfaction. This research is designed to use quantitative approach. The causal relationship across research variables is examined with Structural Equation Modeling-Partial Least Squares (SEM-PLS). Research population is 52 dairy cattle milk cooperatives in East Java. Sampling method is simple random sampling, and after using this sampling to populaton, it results in a sample of 46 cooperatives. Data are collected through questionnaire. Questions on questionnaire are made and processed with Software SmartPLS Version 3.27. Research has given some results: (1) Organizational Learning and Market Orientation have a positive contribution to the increase of Job Satisfaction; (2) Organizational Learning and Market Orientation do not have a positive contribution to the increase of Business Unit Performance; and (3) Job Satisfaction has a positive contribution to the increase of Business Unit Performance at dairy cattle milk cooperatives in East Java.